2019
DOI: 10.1182/hematology.2019000369
|View full text |Cite
|
Sign up to set email alerts
|

Managing the competing risks of thrombosis, bleeding, and anticoagulation in patients with malignancy

Abstract: The association between malignancy and thrombosis has been recognized for over a century and a half. Patients with cancer have an elevated risk of both initial and recurrent venous thromboembolism (VTE) compared with patients without cancer owing to cancer- and patient-specific factors. Recurrent VTE is common despite anticoagulation, presenting additional management challenges. Patients with cancer also have an increased risk of bleeding when on anticoagulants compared with patients without cancer. This bleed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 62 publications
0
38
0
Order By: Relevance
“…Balancing the scales of bleeding and thrombotic risk in the cancer patient presents unique challenges [ 83 ]. Although we have the various cancer-associated VTE risk stratification scores, the present and future bleeding risk must be considered, including risks associated with radiation therapy, chemotherapy-induced thrombocytopenia and other concerns.…”
Section: Implications Of Tumor Molecular Aberrations On the Use Ofmentioning
confidence: 99%
“…Balancing the scales of bleeding and thrombotic risk in the cancer patient presents unique challenges [ 83 ]. Although we have the various cancer-associated VTE risk stratification scores, the present and future bleeding risk must be considered, including risks associated with radiation therapy, chemotherapy-induced thrombocytopenia and other concerns.…”
Section: Implications Of Tumor Molecular Aberrations On the Use Ofmentioning
confidence: 99%
“…6,8 In accord with the stepwise analytic procedures (stages 1 through 5), algorithms exist that guide the testing pathway and allow a rational diagnostic workup. These algorithms encompass both bleeding [9][10][11][12][13][14][15][16] and thrombotic 15,[17][18][19][20][21][22] disorders or abnormal findings in laboratory hemostasis. For example, in case of a prolonged aPTT, a rather frequent and multicausal finding in hemostasis laboratory diagnostics, 23 the algorithms direct the type and sequence of tests to permit a clear differential diagnosis and to identify the precise cause of the abnormality, including rare clinical conditions.…”
Section: Principles Of Laboratory Hemostasis Testingmentioning
confidence: 99%
“…Balancing the scales of thrombotic and bleeding risks, in the oncology patient population presents unique challenges [45].…”
Section: Implications For the Use Of Primary Thromboprophylaxis Or Exmentioning
confidence: 99%
“…In fact, large observational or retrospective cohort studies have shown an elevated risk of thrombosis in patients with ALK and ROS1 rearranged non-small-cell lung cancer (NSCLC) compared to those without such rearrangements. Therefore, clinicians should consider a lower threshold to apply thromboprophylaxis in patients with NSCLC and ALK or ROS1 rearrangements, who otherwise have traditional VTE risk scores in the intermediate risk range [45]. Similarly, in the case of molecular aberrations in other tumors, the knowledge that a patient may be at increased thrombotic risk due to the underlying tumor genotype is another valid piece of information that the clinician should consider when determining if a patient can possibly benefit from thromboprophylaxis [45].…”
Section: Implications For the Use Of Primary Thromboprophylaxis Or Exmentioning
confidence: 99%
See 1 more Smart Citation